2001
DOI: 10.1182/blood.v97.10.3268
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in the CD36 binding domain of the Plasmodium falciparum variant antigen are responsible for the inability of chondroitin sulfate A adherent parasites to bind CD36

Abstract: Adhesion of mature Plasmodium falciparum parasitized erythrocytes to microvascular endothelial cells or to placenta contributes directly to the virulence and severe pathology of P falciparum malaria. Whereas CD36 is the major endothelial receptor for microvasculature sequestration, infected erythrocytes adhering in the placenta bind chondroitin sulfate A (CSA) but not CD36. Binding to both receptors is mediated by different members of the large and diverse protein family P falciparum erythrocyte membrane prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 42 publications
(85 reference statements)
3
55
0
Order By: Relevance
“…This interaction is mediated by the M2 region of the CIDR1 domain of PfEMP1. 36 In this study, we show that a 179-amino acid peptide from the CIDR domain of MCvar1 PfEMP1 inhibited and reversed the adhesion of IRBCs from multiple clinical parasite isolates to HDMECs under flow conditions in vitro and to human microvessels in skin grafts on SCID mice in vivo. This is the first demonstration that cytoadherence of diverse wild-type parasite strains on a physiologic substratum can be inhibited by a single parasite protein under shear stress.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This interaction is mediated by the M2 region of the CIDR1 domain of PfEMP1. 36 In this study, we show that a 179-amino acid peptide from the CIDR domain of MCvar1 PfEMP1 inhibited and reversed the adhesion of IRBCs from multiple clinical parasite isolates to HDMECs under flow conditions in vitro and to human microvessels in skin grafts on SCID mice in vivo. This is the first demonstration that cytoadherence of diverse wild-type parasite strains on a physiologic substratum can be inhibited by a single parasite protein under shear stress.…”
Section: Discussionmentioning
confidence: 98%
“…This protein is the homologous region to MC-179 in the CIDR1 domain from the FCR3-CSA strain of P falciparum. This CIDR1 domain is known not to bind to CD36 25 and served to demonstrate the specificity of the assay to detect proteins that specifically bind to CD36. Furthermore, PpMC-179 inhibited the binding of IRBCs from the FMG strain to recombinant CD36 in a static binding assay, whereas an unrelated yeast recombinant protein yPyCSP had no effect ( Table 1).…”
Section: Cd36 Bindingmentioning
confidence: 99%
“…These parasites are known to express antigenically variant PfEMP1s (22) (MCvar1 1273-1714 ; accession no. AAB60251) were cloned and grown in culture as described previously (23).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the antibody response is directed to the M2 region in MC CIDR1. The CIDR1 domain can be divided to three parts, the M1, M2, and M3 regions, where M2 represents the minimal CD36 binding domain (23). We examined whether DNA immunization with the full-length CIDR1 directed most of the antibody response to the M2 region or to the M1 and M3 regions.…”
Section: Dna Immunization Induces An Antibody Response To the Minimalmentioning
confidence: 99%
“…The region within PfEMP-1 responsible for CD36 binding was initially mapped in the Malayan Camp (MC) line of P. falciparum to a 179-amino-acid fragment (MC-r179) within the central M2 region of the CIDR␣ domain (4) and confirmed using other parasite lines (15,31). Comparison of various CIDR domains from several strains of P. falciparum showed that this cysteine-rich "minimal" binding domain had a conserved sequence, including the presence of five cysteine residues forming the motif CX 8 CX 3 CX 3 CXC (Fig.…”
mentioning
confidence: 99%